A New Simple Conjugate Gradient Coefficient for Unconstrained Optimization - Mustafa, Mamat; Norrlaili, Shapiee; Mohd Rivaie, Mohd Ali (HIKARI Ltd., 2015)
Conjugate gradient (CG) methods are important in solving unconstrained optimization especially for large-scale unconstrained optimization. In this paper, we proposed a new simple CG coefficient. The global convergence result is established by using exact line search. Numerical results based on number of iterations and CPU time. Numerical result shows that our method is efficient when compared to the other CG coefficients for a given standard test problems.